Incorporating gender-inclusive language in undergraduate courses on anatomy and physiology of the speech mechanism - Smith, Julian; Smith, Keith; White, Evan (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: Competence (human resources); Cultural competence; Curriculum; English language; Language acquisition; Mechanism (biology); Multiculturalism; dept.cmd

Reliability of Lingual Swallow Pressure Measurements in Healthy Older and Younger Adults - Smith, Julian; Murray, Kelsey; Szynkiewicz, Sarah; Wasiuk, Peter; Dalton, M; Thompson, Kirsty; Kamarunas, Erin (Journal of Oral Rehabilitation, 2025)
Keywords: Bolus (digestion); Mastication; Measurement device; Reliability (semiconductor); Swallowing; dept.cmd; dysphagia; lingual strength; reliability; swallow pressureswallowingtongue strength

Imaging of the Velopharynx: Nasopharyngoscopy - Kummer, Ann W.; Mabry, Kelly (Cleft Palate and Velopharyngeal Dysfunction: A Multidisciplinary Approach to Evaluation and Management, 2025)
Nasopharyngoscopy is a minimally invasive endoscopic procedure that allows visual observation and analysis of the velopharyngeal mechanism during speech. It can be used to assess both anatomic and physiologic abnormalities of the velopharyngeal valve. In cases of suspected velopharyngeal insufficiency (VPI), nasopharyngoscopy is particularly useful in determining the size, location, and cause of the velopharyngeal opening. This information is very important for surgical planning. Nasopharyngoscopy is also useful in the assessment of secondary surgery that was done for VPI. It can help determine the need for revision and the type of revision surgery that is most likely to be successful. The purpose of the chapter is to explain how nasopharyngoscopy is used in the evaluation of velopharyngeal function. This chapter includes specific tips for achieving a successful examination in children as young as age 3. Finally, important observations from nasopharyngoscopy are described. © 2025 The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Hypernasality; Instrumental assessment; Medicine; Nasal emission; Nasendoscopy; Nasopharyngoscopy; Resonance disorder; Velopharyngeal dysfunction; Velopharyngeal incompetence; Velopharyngeal insufficiency; Velopharyngeal valve; dept.cmd

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy